Habit and physical activity: Theoretical advances, practical implications, and agenda for future research - Hagger, Martin (Elsevier BV, 2018)
Objective: Understanding habits may inform intervention development aimed at promoting physical activity maintenance for long-term health. In the present article, I review theory and research on habits applied to physical activity. I provide an overview of contemporary conceptualizations of habit and habit theory; address whether or not physical activity can be habitual; review perspectives on how physical activity habits develop; summarize research on effects of physical activity habits; identify intervention strategies effective in promoting physical activity habits; and propose an agenda for future research on physical activity habits. Design and Methods: Conceptual and narrative review. Discussion and conclusion: My overview begins with the definition and conceptualization of habit. Habits are defined as specific behavioral responses co-occurring with environmental cues or contextual features. Habitual behaviors such as physical activity are represented in associative memory, and experienced as low effort, automatic, and independent of goals and intentions. Habits are developed through repeated experience of the activity in stable contexts. The activity is initially controlled by goals and rewards, but control shifts to non-conscious, automatic processes as habits develop. Interventions to develop habits require promotion of self-regulatory skills that enable repeated experience of the activity in conjunction with stable cues or contexts. I propose strategies based on research on habit and self-regulation that may inform interventions to promote physical activity habits. I also propose an agenda for future research on habit in physical activity, which includes developing an integrated theory of habit, adopting innovative measures and designs, and testing interventions to develop habits.